2001
DOI: 10.1002/1529-0131(200103)44:3<595::aid-anr108>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor ? activators inhibit interleukin-1?-induced nitric oxide and matrix metalloproteinase 13 production in human chondrocytes

Abstract: Objective To determine the effects of peroxisome proliferator–activated receptor γ (PPARγ) agonists on interleukin‐1 (IL‐1) induction of nitric oxide (NO) and matrix metalloproteinase 13 (MMP‐13) in human chondrocytes. Methods PPARγ expression and synthesis in human chondrocytes were determined by reverse transcriptase–polymerase chain reaction (RT‐PCR) and immunohistochemistry, respectively. Chondrocytes were cultured with IL‐1β, tumor necrosis factor α (TNFα), and IL‐17 in the presence or absence of PPARγ ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
125
0
7

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 198 publications
(138 citation statements)
references
References 60 publications
(84 reference statements)
6
125
0
7
Order By: Relevance
“…More specifically, with regard to the pathophysiologic mechanisms of arthritis, studies have demonstrated that the activation of PPAR␥ could inhibit a number of important pathways responsible for the structural changes that occur during OA. For instance, PPAR␥ agonists were found to inhibit production of IL-1␤, NO, and MMP-13 in vitro in human OA chondrocytes (15,17), and to inhibit MMP-1 and IL-1␤ in human arthritis synovial fibroblasts (16,30). The inhibition of MMP-1 production was found to be associated with a reduction in activator protein 1 (AP-1) binding activity (16).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More specifically, with regard to the pathophysiologic mechanisms of arthritis, studies have demonstrated that the activation of PPAR␥ could inhibit a number of important pathways responsible for the structural changes that occur during OA. For instance, PPAR␥ agonists were found to inhibit production of IL-1␤, NO, and MMP-13 in vitro in human OA chondrocytes (15,17), and to inhibit MMP-1 and IL-1␤ in human arthritis synovial fibroblasts (16,30). The inhibition of MMP-1 production was found to be associated with a reduction in activator protein 1 (AP-1) binding activity (16).…”
Section: Discussionmentioning
confidence: 99%
“…PPAR␥ agonists have been shown to be potent inhibitors of the synthesis of inflammatory cytokines, such as IL-1␤, TNF␣, and IL-6, by monocyte/ macrophage cells and other cell types (18,40). The effects of pioglitazone in terms of reducing the synthesis of the MMPs, including MMP-1, could be attributed to multiple mechanisms (15,16). The reduction in the activity of both the p38 and the ERK-1/2 pathways is likely to be a very important mechanism, since these pathways are predominant in the regulation of expression of MMP-1 in chondrocytes (17,21,42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PPARG2 activation prevents the expression of several inflammatory genes responsible for the pathogenesis of OA, including interleukin-1β, inducible nitric acid synthase, cyclo-oxygenase-2 and microsomal prostaglandin-E2 synthase-1 4–7. There is also some evidence to suggest that PPARG2 activation may be chondroprotective by negatively regulating the expression of matrix metalloproteinase-1 and matrix metalloproteinase-13 and by preventing proteoglycan degradation 4589. It has also been shown that treatment with a PPARG2 activator, pioglitazone, shows beneficial effects in an experimental model of OA 10.…”
mentioning
confidence: 99%